Poor outcome reporting in medical research; building practice on spoilt grounds - Mantziari, Styliani; Demartines, Nicolas (Annals of Translational Medicine, 2017)
Published medical literature forms an ever-expanding web of information, available to patients, clinicians and all healthcare providers in everyday practice. Data from some of these publications, especially from high-impact journals, may be used to guide therapeutic decisions. Moreover, these data will be used for future studies’ design, such as for sample size calculations based on previously published size effects (1) or for conducting systematic reviews and metaanalyses, that represent the highest level of evidence in Medical Research (2). Unfortunately, a growing volume of evidence suggests high rates of poor selection and reporting of research outcomes; the reasons are either inadequate formulation of the research question or deliberate selection of outcomes presented depending on their observed results (outcome reporting bias), but in any case this is a rather worrisome phenomenon that needs to be properly addressed in order to protect transparency and reliability of health care research.